Understanding Islamic Financial Technology Adoptin in Indonesia: The Integration of Utaut, Es-Qual, and Religiosity - Wibowo, Dedi; Hariri Bakri, Mohammed (Journal of Accounting and Finance Management, 2024)
Indonesia has largest Muslim population in the world, holds immense potential to lead the global technology based financial service revolution. However, the current landscape presents limitated market share. Out of 330 licensed fintechs, only 28 adhere to Sharia economic principles. This study aimed to to provide a conceptual model and unravel the factors shaping Behavioral Intentions (BI) in the use of Islamic Fintech in Indonesia. Additionally, it sought to assess the mediating effects of BI on the relationship between UTAUT2, Religiosity, and Service Quality of Islamic fintech, impacting Use Behavior (UB). Questionnaires was administered from 539 respondents, forming the basis for primary data collection. Descriptive statistics were used for data analysis, while SEM PLS examined the relationships between variables. This study revealed that BI of Islamic fintech directly influenced by Performance Expectation (PE), Effort Expectation (EE), Social Influence (SI), Habit (HA), Religiosity (RE), and ESQUAL (ESQ), while Facilitating Conditions (FC), HA, and BI significantly affects UB. A pivotal finding was the identification of BI as a mediator in the relationship between RE and ESQ, influencing subsequent UB. These results contribute significantly to the existing knowledge base, offering valuable insights to enhance the performance of Islamic fintech in Indonesia. The proposed factor model not only provides a framework for influencing behavioral intention within the sector but also suggests improvements to operational efficiency and effectiveness. This study is poised to make substantial contributions to the managerial and policy frameworks of Islamic fintech firms, fostering a more robust and responsive industry in Indonesia.